Tailoring the Local Conductivity of TiO2 by X‐Ray Nanobeam Irradiation. (6th May 2019) - Mino, Lorenzo; Bonino, Valentina; Picollo, Federico; Fretto, Matteo; Agostino, Angelo; Truccato, Marco
Abstract: It is well known that intense synchrotron beams can alter the state of materials, but this effect is generally considered undesired radiation damage. The effect of local irradiation of TiO2 rutile single crystals is investigated by a 56 × 57 nm 2 synchrotron X‐ray nanobeam at 17.4 keV. Aside from a transient increase of conductivity due to a photovoltaic‐like process, a nonvolatile localized change of resistance by about 4 orders of magnitude is measured after X‐ray exposure. This effect can be ascribed to the local generation of oxygen vacancies by the X‐ray nanoprobe, which are subsequently ordered by the electric field applied during the acquisition of I – V curves. These results demonstrate that intense synchrotron beams can create oxygen vacancies in materials with tightly bound oxygen atoms, highlighting that X‐ray nanoprobes could become an effective tool for oxide nanofabrication, able to locally tune the material resistivity. For instance, since the localized presence and migration of oxygen vacancies is an essential requisite for redox‐based memristive devices, the possibility to locally induce oxygen vacancies could represent a novel tool for the production of oxide‐based memristive devices, replacing the problematic electroforming step. Abstract : A synchrotron X‐ray nanobeam is employed to directly write sub‐micrometer conductive channels comprising oxygen vacancies on TiO2 crystals. This X‐ray nanopatterning process is based on the modification of the local oxygen content and can represent a promising tool for the nanofabrication of oxides, tuning the material resistivity. X‐ray nanopatterning can enable the production of new memristive devices.